1979
DOI: 10.1007/bf01235886
|View full text |Cite
|
Sign up to set email alerts
|

Utrastructural and morphometric studies of delta cells in pancreatic islets from C57BL/Ks diabetes mice

Abstract: An ultrastructural and immunocytochemical study was undertaken to elucidate the temporal and quantitative aspects of the changes occurring in the delta cells in the pancreatic islets of C57BL/KsJ db/db (diabetes) mice. Electron microscopy revealed that prior to the major topographical redistribution of delta cells from their peripheral location to the islet interior, long delta cell filopodial extensions penetrated into the islet, greatly increasing the area of surface contact between delta cells and hypersecr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
23
1

Year Published

1984
1984
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 30 publications
9
23
1
Order By: Relevance
“…This might lead to overestimation of β-cell contribution to the total ZRL1 fluorescence in live islets. However, δ-cells comprise less than 10% of total pancreatic islet content (Leiter et al, 1979). In agreement with a minor contribution of δ-cells, the ratio of the α-cell to β-cell mass in live islets calculated based on FQA is not significantly different from that obtained by IHC from pancreas slices isolated from mice with the same age in multiple experimental trials ( Figs 3D and 6F).…”
Section: Discussionsupporting
confidence: 79%
“…This might lead to overestimation of β-cell contribution to the total ZRL1 fluorescence in live islets. However, δ-cells comprise less than 10% of total pancreatic islet content (Leiter et al, 1979). In agreement with a minor contribution of δ-cells, the ratio of the α-cell to β-cell mass in live islets calculated based on FQA is not significantly different from that obtained by IHC from pancreas slices isolated from mice with the same age in multiple experimental trials ( Figs 3D and 6F).…”
Section: Discussionsupporting
confidence: 79%
“…The histological studies of Petkov et al (34) showed that islet damage in diabetic P. obesus is similar to that found in human diabetes, BB Wistar rats, and C57BL/KS mice (11,23,42). We have found that the mitochondrial potentiometric dye Rh123 appears to be an excellent tool for visualizing cell damage in intact islets, as it is highly permeable and specific to mitochondria.…”
Section: Discussionsupporting
confidence: 72%
“…On the other hand, there is an increase in volume density of glucagon, somatostatin and pancreatic polypeptide secreting cells with an alteration in their peripheral localization (Baetans, Stefan, Ravazzola, Malaisse-Lagae, Coleman & Orci, 1978). Leiter, Gapp, Eppig & Coleman (1979) Assays have demonstrated that these mutants are hyperglucagonaemic (Stearns & Benzo, 1978) and that pancreatic somatostatin is elevated (Makino, Matsushima, Kanatsuka, Yamamoto, Kumagai & Nishimura, 1979). Very recently Berelowitz & Frohman (1983) have reported on immunoreactive neurotensin in the db/db pancreas.…”
Section: Islets Of Langerhans Functionmentioning
confidence: 99%